Integrated Investment Appraisal of Waste Water Facility Project: The Case of a Proposed Waste Water Treatment Plant in South Africa - Eskandar, Nariman (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
This analysis is an evaluation study of a Water Conservation and Resource Plan with Infrastructure Execution located in South Africa. The Cost-Benefit Analysis (CBA) in this appraisal study contains a comprehensive analysis of the Wastewater treatment plant project from various perspectives that mainly involves the project's financial, economic, stakeholder and risk analyses. The influences of each main stakeholders are measured to assess the project's potential costs and benefits. The recycling project benefits will be assessed against the option of purchasing water for use by the mining company and its large resident community of workers and their families. Keywords: Water, Wastewater, South Africa, Water treatment, Infrastructure, Cost Benefit Analysis, Integrated Investment Appraisal.

ÖZ: Bu analiz, Güney Afrika'da bulunan Altyapı Yürütmeli Su Koruma ve Kaynak Planının bir değerlendirme çalışmasıdır. Bu değerlendirme çalışmasındaki Maliyet Fayda Analizi (CBA), temel olarak projenin finansal, ekonomik, paydaş ve risk analizlerini içeren çeşitli perspektiflerden Atıksu arıtma tesisi projesinin kapsamlı bir analizini içerir. Her ana paydaşın etkileri, projenin potansiyel maliyetlerini ve faydalarını değerlendirmek için ölçülür. Geri dönüşüm projesinin faydaları, maden şirketi ve büyük yerleşik işçi topluluğu ve aileleri tarafından kullanılmak üzere su satın alma seçeneğine göre değerlendirilecektir. Anahtar Kelimeler: Su, Atıksu, Güney Afrika, Su arıtma, Altyapı, Maliyet-Fayda Analizi, Entegre Yatırım Değerlendirmesi.
Master of Science in Economics. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2021. Supervisor: Prof. Dr. Glenn Paul Jenkins.
Keywords: Political Science and International Relations; Waste Water Treatment - Water Conservation - Economic Aspects - South Africa; Water; Water treatment; Infrastructure; Cost Benefit Analysis; Integrated Investment Appraisal; Wastewater; South Africa